Fairest eaudiobook Levana's story. - Meyer, Marissa (The Lunar Chronicles, 2015)
The #1 New York Times Bestselling Series! Mirror, mirror on the wall, Who is the fairest of them all? Fans of the Lunar Chronicles know Queen Levana as a ruler who uses her "glamour" to gain power. But long before she crossed paths with Cinder, Scarlet, and Cress, Levana lived a very different story – a story that has never been told . . . until now. Marissa Meyer spins yet another unforgettable tale about love and war, deceit and death. This extraordinary book includes full-color art and an excerpt from Winter , the next book in the Lunar Chronicles series.